The Impact of Special Autonomy Fiscal Policy on Papua's Economic Development - Sanggrangbano, Agustina; Antoh, Agustina Ester; Timisela, Stephanny Inagamma (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2024)
Economic development needs to be viewed as a process that is interrelated, and interconnected and mutually influences the factors that produce development itself. The movement of economic development in a region is indicated by regional economic growth in that region. It is believed that Papua's economic growth can be stimulated by the special autonomy fiscal policy implemented by the Papuan government. This research aims to analyze the impact of fiscal policy through education spending from special autonomy funding sources together with other economic variables on Papua's economic growth by applying the Neoclassical Solow growth model and the growth model from Mankiw, et al. (1992). This research was conducted using secondary data from nine districts/cities in Papua Province in the 2013-2021 period which used panel data regression and for analysis using the Feasible Generalized Least Square (FGLS) approach with either the Panel Corrected Standard Error (PCSE) model or the Seemingly Unrelated Regression (SUR) model. The research results show that education spending variables and other economic variables have a significant impact on spurring Papua's economic growth. This shows that the special autonomy fiscal policy can drive Papua's economic development.